Unemployment Insurance and Employment - Deere, Donald R. (Journal of Labor Economics, 1991)
This article examines the impact of unemployment insurance (UI) on the allocation of labor across industries. An overlooked aspect of UI is the effect of imperfect experience rating on hiring. Firms in more stable industries generally pay more into the UI system than their workers ever receive in benefits, thus subsidizing more volatile industries. The results indicate that industry employment shares are significantly affected by UI and that there is a net shift of resources from the service industry to the construction industry. The estimates also imply that layoff unemployment is increased by about 5% because of UI-induced employment shifts.